Evaluation of the applicability of Lewin's force field analysis in the implementation of the Financial Sector Charter at Standard Bank - Skepe, Siphelo (Rhodes University, Faculty of Commerce, Rhodes Business School, 2013)
According to the Financial Sector (FS) Charter, in August 2002, at the NEDLAC Financial Sector Summit, "the financial sector committed itself to the development of a Black Economic Empowerment (BEE) charter. It made this commitment, noting that: "Despite significant progress since the establishment of a democratic government in 1994, South African society remains characterised by racially based income and social services inequalities. This is not only unjust, but inhibits the country's ability to achieve its full economic potential. BEE is a mechanism aimed at addressing inequalities and mobilising the energies of all South Africans. It will contribute towards sustained economic growth, development and social transformation in South Africa. Inequalities also manifest themselves in the country's financial sector. A positive and proactive response from the sector through the implementation of BEE will further unlock the sector's potential, promote its global competitiveness, and enhance its world class status". Parties of the Financial Sector Charter agreed on the seven pillars below: 1) Human resource management - provide resources to develop skills of black people with the aim of increasing black participation in all levels of management in the sector. 2) Procurement policies - implement a targeted procurement strategy to enhance BEE. 3) Enterprise development - improve the level of support provided to BEE companies in all sectors of the economy. This would be achieved through skills transfer, administration and technical support. 4) Access to financial services - provide affordable financial services to the previously disadvantaged groups and making sure financial services are accessible to these groups. 5) Empowerment financing - work closely with government and government financial institutions to increase resources for empowerment financing. 6) Ownership in the financial sector - 25% of shares in each party of the FS Charter should be owned by black people by 2010. 7) Corporate social investrnent (CSI) - Each financial institution will have to spend 0.5% of their after-tax profit on corporate social investment projects. The projects should be targeted at black groups with a strong focus on transformation. The research evaluates the applicability of Lewin's Force Field Analysis (a change management model) in the implementation of the Financial Sector Charter at Standard Bank of South Africa. It attempts to achieve this by looking at how the Financial Sector Charter is being implemented at Standard Bank. The research looks at three main areas: 1) The "context" of the research problem, by seeking to understand Standard Bank's understanding of the FS Charter, the importance of implementing the FS Charter by the bank, the progress made thus far in the FS Charter implementation and comparison to the BEE scorecards of the other three main bank. 2) The "process", i.e. how the FS Charter is implemented in the bank, the driving and restraining forces of successful implementation of the FS Charter and the lessons learnt. 3) The "outcome" , i.e. benefits of implementing the FS Charter and what could be done to ensure that change management processes are successfully implemented. Personal interviews were used to discover other valuable information which was not available on the bank's published documents, and other related sources such as the Financial Sector Charter document. The sample size for the study was ten Standard Bank employees from different areas of the bank who are either senior managers or directors, in the bank. Internal publications available on the Standard Bank intranet such as the bank's employment equity plans, and the bank's sustainability reports from 2004 to 2011 (Standard Bank, 2004-2011) were analysed for the purpose of the study. The researcher also analysed public documents such as the bank's annual financial reports, bank's equity reports and internal publications on related topics of the research question. Lewin's Forces Field Analysis (FFA) points out that in any environment where change is required; there are both driving and restraining forces that influence the implementation of a change programme. The FFA is a valuable change management tool at trying to transform the behaviour of an individual, and this will lead to transformation of groups and, ultimately the organisation. It also helps to establish the balance between the driving and restraining forces of the change programme. Lewin's (1951) theory put forward the idea that change occurs in three stages: the first stage of change is unfreezing; the second stage is moving and lastly, the third stage is refreezing. In the unfreezing stage, the bank's change management initiatives would need to be directed at giving the individuals a desire and motivation to be ready and open about a planned change initiative. This could be achieved by clearly communicating why change is important, benefits of change and the compelling reasons for change. In moving, the bank would need to give support and confidence to the people affected by change in order to start accepting and buying-in to new perspectives, which enable them to realise that change will improve the current situation. In the refreezing stage, the bank would need to ensure that new patterns of behaviour are reinforced. This will ensure that the changes are applied in everyday business, and this helps create a sense of stability, where those affected by change feel comfortable and confident with the new approach of doing things. The research concludes that managers should recognise the sensitivity around transformation, and should always try to ensure that change management initiatives directed at transformation are unifying, fair and transparent. This should be done to avoid a situation where an employee (or prospective employees) and other stakeholders feel under-appreciated or overlooked because of their gender or race. This demands a carefully crafted and implemented change management programme, whose results will not only unify the bank's employees, but also create a competitive edge for the bank. Lewin's Force Field Analysis (FFA) model is a change management tool that could be used to produce such results.
Keywords: Standard Bank of -- South Africa Limited (1962- ); Banks and banking -- South Africa; Financial services industry -- Law and legislation -- South Africa; Black people -- South Africa -- Economic conditions; Business enterprises, Black -- South Africa; Organizational change -- South Africa